Shareholder Suit as the Corporate Control Strategy of Investment - makharoblishvili, giorgi (PRAWO i WIĘŹ, 2023)
The author analyses one of the major dilemmas of corporate law, which relates to corporate mechanisms for controlling and safeguarding investment. Corporate law creates a systemic matrix, which facilitates the organizational management of the business entity and the activism of the investor. Separating ownership and control by the management of the JSC creates the presumptive risk of unfair action. The managing person is more oriented toward increasing personal profit rather than maximizing the value of the company. Therefore, along with the general mechanisms of internal corporate management of the risk, beyond the competence of the general meeting, it is necessary to equip shareholders with the corporate control mechanism having precise aim. Shareholder suit is one of the mechanisms of controlling and safeguarding the investment, which may be of the following types: direct (individual) suit, indirect (derivative) suit, and class action. A suit is a methodological tool used for initiating liability and restoring infringed rights of shareholders. Classes of the suit are the corporate strategy of investment, which is related to the control function of the shareholder.